Simultaneous detection of diethylstilbestrol and estradiol residues with a single immunochromatographic assay strip. Issue 3 (20th January 2021) - Xu, Zehua; Sun, Tieqiang; He, Hongwei; Liu, Wentao; Fan, Longxing; Zhao, Lingdi; Wu, Xinglin; Han, Zhenyu; Zhang, Yingcun; Wang, Qiangqiang; Ning, Baoan; Gao, Zhixian
Abstract: An immunochromatographic assay (ICA) based on competitive format was developed and validated for simultaneously rapid and sensitive detection of diethylstilbestrol (DES) and estradiol (E2 ) in milk and tissue samples. For this purpose, two monoclonal antibodies raised against those two estrogens were conjugated to gold nanoparticles and were applied to the conjugate pads of the test strip. The competitors of the DES‐BSA/E2 ‐BSA conjugates were immobilized onto a nitrocellulose membrane at two detection zones to form T1 and T2, respectively. The immunochromatographic assay had a visual detection limit of DES at 30 ng/g in milk powder, 25 ng/g in liquid milk, and 25 ng/g in shrimp tissue, respectively, and the results can be judged within 7–10 min. The visual detection limit of E2 was 75 ng/g in milk powder, 65 ng/g in liquid milk, and 60 ng/g in shrimp tissue, respectively, and the results can be judged within 3–4 min. It had advantages in easy operation without requiring sophisticated equipment and specialized skills. By testing thirty milk and shrimp tissue samples from the local market, the method was compared with the HPLC‐MS / MS method, and there was no statistical difference between the two methods. Furthermore, the immunochromatographic assay had good specificity, simple procedure, and low cost. This protocol was well suited for the food safety monitoring and early warning. Abstract : An immunochromatographic assay (ICA) based on competitive format was developed and validated for simultaneously rapid and sensitive detection of diethylstilbestrol (DES) and estradiol (E2 ) in milk and tissue samples. For this purpose, two monoclonal antibodies raised against those two estrogens were conjugated to gold nanoparticles and were applied to the conjugate pads of the test strip.